2004
DOI: 10.1110/ps.04701304
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the conformational transition of a model polyalanine peptide

Abstract: We have investigated the folding of polyalanine by combining discontinuous molecular dynamics simulation with our newly developed off-lattice intermediate-resolution protein model. The thermodynamics of a system containing a single Ac-KA 14 K-NH 2 molecule has been explored by using the replica exchange simulation method to map out the conformational transitions as a function of temperature. We have also explored the influence of solvent type on the folding process by varying the relative strength of the side-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 88 publications
5
115
0
Order By: Relevance
“…These results are consistent with experimental measurements [38] and also with previous theoretical suggestions from other groups [39][40][41]. Here we focus on the α-helix ↔ β-sheet interconversion, which we attempt to characterize in terms of specific order parameters.…”
Section: Introductionsupporting
confidence: 88%
“…These results are consistent with experimental measurements [38] and also with previous theoretical suggestions from other groups [39][40][41]. Here we focus on the α-helix ↔ β-sheet interconversion, which we attempt to characterize in terms of specific order parameters.…”
Section: Introductionsupporting
confidence: 88%
“…Our results show that both a repulsive db and a physically realistic range of cm attraction of ∼5.0Å between methyl or methylene groups tend to favor β over α structures, at least for the polyalanine, polyvaline, and polyleucine chains we have studied. This finding may help to assess prior studies that used effective ranges of cm attraction as large as 6.5Å [31,32]. db's arise from empty spaces created by water exclusion between hydrophobic groups [37][38][39][40]42] and are the hallmark of interactions between nonpolar groups [33,34,[36][37][38][39][40][41][42][43] that are partially exposed to water.…”
Section: Discussionmentioning
confidence: 99%
“…An early simulation of a 12mer polyalanine indicated that its ground state was an α helix in vacuum and a β hairpin in aqueous solution [30]. However, subsequent simulations of aqueous short hydrophobic-polar [31] and polyalanine [32] peptides using different potential functions predicted an α-helical ground state except for very high hydrophobic interaction strengths [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobic interactions and hydrogen bonding are the primary driving forces that cause such assembly in 17H6; hairpin substructures have also been reported for other alanine-rich sequences. [48][49][50] Hydrophobic interactions promote the exclusion of water and other hydrophilic species by collapse of the hydrophobic alanine residues. Hydrogen bonding within the β sheets stabilizes this structure, which incorporates more 17H6 monomer units in a similar manner and leads to fibril axial fibril growth.…”
mentioning
confidence: 99%